New ambient pressure organic superconductors:. alpha. -(BEDT-TTF) sub 2 (NH sub 4 )Hg(SCN) sub 4 ,. beta. m-(BEDO-TTF) sub 3 Cu sub 2 (NCS) sub 3 , and. kappa. -(BEDT-TTF) sub 2 Cu(N(CN) sub 2 )Br - Wang, H. H.; Beno, M. A.; Carlson, K. D.; Geiser, U.; Kini, A. M.; Montgomery, L. K.; Thompson, J. E.; Williams, J. M. (Argonne National Laboratory, 1990)
More than one hundred and twenty conducting salts based on the organic donor-molecule BEDT-TTF are known, where BEDT-TTF is bis(ethylenedithio)tetrathiafulvalene (abbreviated herein as ET). Several of the early salts possessed tetrahedral and octahedral anions, such as (ET)sub 2ClOsub 4(TCE), (ET)sub 2PFsub 6, (ET)sub 2ReOsub 4, and (ET)sub 2BrOsub 4. The perchlorate salt is metallic to 1.4 K,{sup 1} and the perrenate derivative was the first ET based organic superconductor (Tc 2 K, 4.5 kbar). Since the discovery of ambient pressure superconductivity in {beta}-(ET)sub 2Isub 3 (Tc 1.4 K),{sup 5} other isostructural {beta}-(ET)sub 2X salts have been prepared with higher Tc's. A structure-property correlation for the {beta}-type salts has been reviewed in this volume; it predicts that Tc's higher than 8K are possible if {beta}-salts with linear anions longer than Isub 3{sup {minus}} can be synthesized. During the search for new linear anions, a variety of compounds with discovered with polymeric anions. The report of superconductivity in {kappa}-(ET)sub 4Hgsub 3Xsub 8 (X = Cl, Tc 5.4 K 29 kbar and X = Br, Tc 4.3 K ambient pressure and 6.7 K 3.5 kbar) and {kappa}-(ET)sub 2Cu(NCS){sub 2} (Tc 10.4 K) further stimulated the search for novel polymeric anions. A general synthetic strategy for preparing new salts containing polymeric anions is to couple a coordinatively unsaturated neutral transition metal halide/pseudohalide with a simple halide or pseudohalide during an electrocrystallization synthesis. In this article, the authors discuss three new ambient pressure organic superconductors with novel polymeric anions, {alpha}-(ET){sub 2}(NHsub 4)Hg(SCN){sub 4}, betam-(BO)sub 3Cusub 2(NCS){sub 3} and {kappa}-(ET)sub 2Cu(N(CN){sub 2})Br. 48 refs., 8 figs., 2 tabs.